Estimation of lactoferrin levels in gingival crevicular fluid before and after periodontal therapy in patients with chronic periodontitis - Anasuya V Kivadasannavar; Pushpa S Pudakalakatti; Sanjeevini A Hattarki; Soumya S Kambali (Wolters Kluwer Medknow Publications, 2014)
Background: The lactoferrin (LF) is an iron binding protein present specifically and in abundance in the secondary granules of polymorphonuclear leukocytes (PMN's). It has been suggested that LF in crevicular fluid is a useful marker of PMN activity. Hence, this study aimed to estimate the levels of LF in gingival crevicular fluid (GCF) before and after surgical therapy in chronic periodontitis patients to assess the validity of LF in monitoring of treatment results. Materials and Methods: A total of 30 patients with chronic periodontitis having probing depth of ≥5 mm who were scheduled for periodontal surgery were included in the study. The clinical parameters were recorded and GCF samples were obtained 2 weeks after scaling and root planing and 2 weeks after conventional flap technique. The samples collected were then assayed for LF using Enzyme-linked immunosorbent assay (ELISA). Results: The results showed that LF levels decreased significantly from 266.53 ± 75.86 to 195.47 ± 74.53 after scaling and root planing. There was further significant reduction in LF levels to 90.42 ± 32.89 following 2 weeks of periodontal surgery, indicating decrease in inflammation. Conclusion: There is a significant reduction in GCF LF levels following periodontal surgery. Hence, LF levels in GCF could serve as a useful marker for monitoring of periodontal treatment results.